Testing quantum gravity with primordial gravitational waves - Gianluca Calcagni; Leonardo Modesto (Journal of High Energy Physics)
Abstract We propose a testable alternative to inflation directly built in a very general class of ultraviolet complete theories of quantum gravity enjoying Weyl invariance. After the latter is spontaneously broken, logarithmic quantum corrections to the action make both the primordial tensor spectrum (from graviton fluctuations) and the scalar spectrum (from thermal fluctuations) quasi scale invariant. We predict a scalar spectral index n s which only depends on two parameters and is consistent with observations, a tensor index n t = 1 − n s > 0, and, if the fundamental energy scale of the theory Λ* = M Pl is of order of the Planck mass, a tensor-to-scalar ratio r 0.05 ≈ 0.01 detectable by BICEP Array and LiteBIRD in the immediate or near future, respectively, and a blue-tilted stochastic gravitational-wave background observable by DECIGO in the further future. From the observational constraint r 0.05 < 0.036, we also find the lower bound Λ* > 8.5 × 1010 GeV, much stronger than any previous one for this class of theories.